Comparative study on the effect of alkali pretreatment technique on removal of lignin and reducing sugar production from different biomass / Jason Angkin Johnady and Dr. Siti Sabrina Mohd Sukri - Johnady, Jason Angkin; Mohd Sukri, Siti Sabrina (2020)
In Malaysia, biomass is generated every year via wastes from agriculture mainly via harvesting and is available in abundance. Rice husks are an example of biomass which are considered as wastes are disposed of improperly as the husks were burned by farmers which resulted in environmental pollution. To address this issue, several researches are continuously carried out to harness the potential of biomass as one of the alternative sources of energy and as a low-cost biosorbent and many more. Generally, biomass is made up of complex lignocellulosic structure comprising of cellulose, hemicellulose and lignin. Prior to accessing cellulose in biomass, it is imperative that lignin is broken down and removed. Thus, there is a need for biomass to undergo chemical pretreatment. There are two most commonly used modes of pretreatment used for delignification of lignocellulosic biomass. The modes of pretreatment are acidic pretreatment and alkali pretreatment. Commonly, analysis of reducing sugars utilizes the Dinitrosalicyclic acid (DNS) method developed by Miller (1959). The treated samples of black liquor from the experiment were analyzed using UV-vis spectrophotometer. This research will evaluate the effectiveness of alkali pretreatment on lignin removal from several biomass using sodium hydroxide and calcium hydroxide. Removal of lignin and reducing sugar production is evaluated from collection of data of several studies. NaOH was found to be the best alkali for alkaline pretreatment because it works at decreased temperatures and also exhibits a remarkable capacity of delignification in relation to its severity.